Recent Monetary Legislation - Laughlin, J. Laurence (Journal of Political Economy, 1900)
IT has been repeated bv the public press, and assumed by the country, chiefly on the basis of reports emanating from Washington, that the act of March I4, I900, whatever may have been its shortcomings in other directions, has at least firmly established the gold standard in the United States. The belief is generally prevalent that the election of a president pledged to the cause of free silver would no longer be a source of danger to our monetary system, because the gold standard has been placed by the new legislation beyond the reach of executive control; that the mere action of a future Secretary of the Treasury hostile to gold could not cause public or private obligations to be paid in silver; and that nothing could now be done for silver except by new and positive legislation, a contingency, which would be impossible so long as the Senate and the Executive favor gold. Hence we are assured that we may rest free from all danger of the "silver issue," which we hear on all sides is now " dead." On the strength of this belief, political lines are being drawn, and a plan of campaign is being formed. That there has been a subtle game of politics played